Determining suitability of pro-and anti-cultural literary texts for a specific interpretive community using HRV Biofeedback at Taibah university - Yousaf, Iftikhar (2019)
This study deals with the measurement of comparative impact of the two selected texts “Doctor Faustus” and “Waiting for Godot” on the readers’ emotions by means of Biofeedback. This research aims at checking the viability of biofeedback as a tool to measure emotions of readers generated by the reading of a piece of literature. Embedded within the theoretical background of interpretive communities, the research scientifically evaluates the suitability of texts within cultural perspective. It will help in adopting a particular text for a particular community for teaching and learning purpose in EFL setting. The thesis describes in detail the antithetical themes of the two texts, the link between emotions and literature, the traditional and modern techniques used to measure emotions, and the functions of biofeedback technology to be used in measuring the physiological changes that occur in the reader while reading pro-cultural and anti-cultural texts. A comprehensive literature review of all the elements has been presented which are integral to this research. Since this study is an amalgam of technology and literature, a mixed mode has been used as a method to ensure the validity and reliability of the research process. The antithetical themes have been examined qualitatively while emotions have been measured scientifically in quantitative terms. From the results, it is observed that antithetical themes do exist in both the plays which bring out their pro-cultural and anti-cultural nature within Saudi perspective. Moreover, the opposing texts have an impact on the HRV Power Spectrum Score of the readers, and there is a correlation between the effects of the opposing themes of “Doctor Faustus” and “Waiting for Godot” towards emotional performance, very low frequency (VLF) and high frequency (HF) of coherence score of the readers which vary from text to text. From the findings, a conclusion is derived that HRV Biofeedback may be used as a viable tool to determine the suitability of a text to be prescribed for a specific interpretive community. Based on this conclusion, it is recommended for a smooth process of learning English as a foreign language or a second language to make use of biofeedback technology while prescribing text books devoid of cultural irritants that demotivate the students in Arab culture.